FEASIBILITY ANALYSIS OF ARABICA COFFEE BUSINESS IN MAJU BERSAMA PLANTATION GROUP, BOMOMANI VILLAGE, DOGIYAI REGENCY, CENTRAL PAPUA PROVINCE - Tebai, Natan; Yoga, Tirta; Saputro, Arief Joko; Hra, Petronela (Institute of Computer Science (IOCS), 2025)
This study aims to assess the profitability and operational effectiveness of Arabica coffee (Coffea arabica) cultivation managed by the Maju Bersama Plantation Group in Bomomani Village, Mapia Subdistrict, Dogiyai District, Central Papua. The study was conducted over the course of one month employing a quantitative method through field-based surveys. The collected data were assessed using key indicators, including production costs, income, net profit, and the revenue-to-cost (R/C) ratio. The results show that the total cost of cultivation for one production cycle was Rp. 14,150,000, with a total revenue of Rp.80,000,000, resulting in a net profit of Rp.65,850,000. An R/C ratio of 5.6 indicates that Arabica coffee cultivation is a promising and sustainable economic opportunity for the local community. The study recommends further development by enhancing farmers’ institutional capacity and integrating technological support and government policy to strengthen the Arabica coffee value chain in the Central Papua region.